2013
DOI: 10.4103/2230-8210.109697
|View full text |Cite
|
Sign up to set email alerts
|

Lean body mass-based levothyroxine replacement in young athyrotic patients with differentiated carcinoma of thyroid

Abstract: Objective:The objective of this study was to optimize dose of levothyroxine (LT4) based on lean body mass (LBM) in young athyrotic patients with differentiated carcinoma of thyroid (DCT) which has not been properly addressed in Bangladesh before.Materials and Methods:Sixty patients with DCT (age, range: 20-39 years) having total thyroidectomy followed by radioiodine ablative therapy (RIT) and 23 euthyroid volunteers were recruited. Clinical, biochemical parameters were obtained from all patients after 2 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Different studies 8 , 9 have suggested that LBM has been shown to be superior to other measures of body size for dosage of many drugs. 8 , 9 LBM equals the total weight of a person’s bone and muscles minus their fat weight. 10 Pharmacokinetic parameters are mostly dependent on LBM and most metabolic processes occur within this body compartment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies 8 , 9 have suggested that LBM has been shown to be superior to other measures of body size for dosage of many drugs. 8 , 9 LBM equals the total weight of a person’s bone and muscles minus their fat weight. 10 Pharmacokinetic parameters are mostly dependent on LBM and most metabolic processes occur within this body compartment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, LBM was computed based on validated anthropometric prediction equations for estimation of LBM in Indian men and women 6 in contrast to a few studies 7 - 9 where LBM was measured by dual energy X-ray absorptiometry (DEXA). The use of this prediction equation was simple, reproducible, noninvasive, and inexpensive compared to the estimation of LBM by MRI or DEXA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation